Analisis Indikator Financial Stress Sebagai Alat Untuk Mengukur Tingkat Kestabilan Aspek Keuangan Di Indonesia - Mas Amah (Universitas PGRI Yogyakarta, 2023)
Many elements may influence defining financial sector stability can be a challenge. The sub-stress level of the financial sector can be used as a proxy to measure the soundness of the financial sector. One technique for assessing the stability of the financial sector is the financial stress index, which is a composite index whose elements can be broken down using factor analysis. Because the index is dominated by the banking component which is very sensitive to the volatility of macroeconomic conditions, I conclude that the financial stress index formed from bank variables is the index with the highest significance for financial stability in Indonesia. The inflation rate and BI rate are indicators to assess this condition.